Building Competitive Employees in The Digital Era With Competency-Based Training - Nurhalima, Afdila Santri (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
Non-formal education is currently being intensively provided by various parties and one of them is training, this is because the digital era has created new demands for employees to have relevant and competitive skills, a mismatch between the demands of the ever-changing job market and the skills they possess. by many current employees. Therefore, efforts are needed to deal with this so that employees can survive and continue to progress. One effort that can be made is to improve one's work performance by honing skills, increasing knowledge or insight and how to behave correctly, and to answer these problems competency-based training is one solution that can be done. This article will discuss further about how to build competitive employees in the digital era with competency-based training. The research method that the author uses in this article is library research, namely by collecting various existing sources. In this article, several key points can be concluded, namely: the importance of employee development as a response to rapid changes in the digital era, competency-based training is identified as an effective approach to improving skills in accordance with job demands, competency-based training programs not only improve skills but also contribute to employee motivation and engagement, and employee development programs have the potential to have a positive impact on an organization's competitiveness in the digital era.